Coding Polymorphisms in Zinc Transporter Gene SLC39A12 (ZIP12) Associated with Brain MRI Pattern Differences Have Reduced Zinc Transport Activity. (29th May 2020) - Chambers, Emily; Clarke, Stephen; Lucas, Edralin; Lucas, Edralin; Stoeker, Barbara; Chowanadisai, Winyoo; Bettaieb, Ahmed; Agidew, Worknah
Abstract: Objectives: Zinc is important for brain function. The SLC39A12 gene encodes ZIP12, which is a zinc transport protein highly expressed in the brain. Our goal is to determine whether human slc39a12 coding polymorphisms associated with differences in susceptibility-weighted brain MRI (swMRI) patterns affect zinc transport ability. Methods: We used summary statistics for a genome-wide association study (GWAS) on swMRI patterns for caudate, putamen, and pallidum of 7778 human subjects aged 40–69 years from the UK BioBank. Human SLC39A12 coding polymorphisms rs10764176 and rs72778328 were associated with a reduction in relaxation spin time during swMRI in the putamen or pallidum but not caudate and met a significance cutoff of P < 5.0 × 10–8. Haploblock determination and linkage disequilibrium (LD) between the variants was determined by SNPclip, LDmatrix, and LDpair software and the European 1000 genomes LD reference panel. The effects of the ZIP12 polymorphisms on cell zinc status and zinc uptake were measured in Chinese hamster ovary (CHO) cells transfected with the reference ZIP12 version or coding variants. Cell zinc status was assessed after 18 hours by metal-response element reporter activation (n = 8). Cell zinc uptake activity was measured by stable isotope Zinc-70 uptake (n = 6) relative to endogenous Zinc-68 content using inductively coupled plasma mass spectrometry (ICP-MS). Statistical comparisons were performed using ANOVA. Significance was set at P < 0.05. Results: Variants rs10764176 and rs72778328 are present on independent haploblocks and are in linkage equilibrium with each other. Variants rs10764176 and rs72778328 have a reduction in MRE reporter activation (41.7% [ P < 0.05] and 55.6% [ P < 0.01], respectively) and in exogenous Zinc-70 uptake after 20 minutes (37.6% [ P < 0.001] and 54.2% [ P < 0.001], respectively) compared to the reference ZIP12. Conclusions: Variants rs10764176 and rs72778328 are on distinct haploblocks. These ZIP12 coding variants that are associated with altered brain swMRI patterns also have reduced zinc uptake activity. Funding Sources: This work was funded by grants from the Oklahoma Center for the Advancement of Science and Technology and the Oklahoma Agricultural Experiment Station.